Evolution of coronary stents in patients with diabetes: are clinical outcomes still improving? - Kassimis, G; De Maria, G; Patel, N; Banning, A (Expert Reviews Ltd., 2014)
Diabetic patients are prone to diffuse and accelerated atherosclerosis, which increases the likelihood of requiring myocardial revascularization. Diabetes mellitus is a strong risk factor for restenosis following coronary stenting, with greater need for repeat revascularization and inferior clinical outcomes. Despite the recent advances in drug-eluting stent technology, diabetic patients are still at higher risk of adverse clinical events after coronary angioplasty. The focus of this review is to describe the evolution of the percutaneous management of diabetic patients with coronary artery disease and to define if any real progress has been made in terms of safety and efficacy with the use of the second generation drug-eluting stents in this high-risk population.